2023
DOI: 10.1007/s40808-022-01670-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association between air pollutants’ concentration and meteorological parameters in a rapidly growing urban center of West Bengal, India: a statistical modeling-based approach

Abstract: The ambient air quality in a city is heavily influenced by meteorological conditions. The city of Siliguri, known as the “Gateway of Northeast India”, is a major hotspot of air pollution in the Indian state of West Bengal. Yet almost no research has been done on the possible impacts of meteorological factors on criterion air pollutants in this rapidly growing urban area. From March 2018 to September 2022, the present study aimed to determine the correlations between meteorological factors, including daily mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…Residents may have become acclimated to the city's water, air, and noise pollution, or consider these problems unavoidable in an urban environment, which is one explanation for this conclusion. This is consistent with earlier studies that identified environmental pollution as a significant issue in Siliguri [39,[99][100][101]. However, addressing environmental pollution is essential for ensuring sustainable growth and raising the standard of living for locals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Residents may have become acclimated to the city's water, air, and noise pollution, or consider these problems unavoidable in an urban environment, which is one explanation for this conclusion. This is consistent with earlier studies that identified environmental pollution as a significant issue in Siliguri [39,[99][100][101]. However, addressing environmental pollution is essential for ensuring sustainable growth and raising the standard of living for locals.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, the outcomes pertaining to environmental contamination exhibit a degree of unexpectedness [40]. The absence of a noteworthy correlation between pollution and contentment may be attributed to diverse factors, including the residents' acquiescence to specific degrees of pollution as a compromise for inhabiting an urban setting [37,100,101]. This offers a prospect to explore the psychological and social factors that could potentially impact the perceptions and attitudes of inhabitants towards pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 It is estimated that in India there were about 1.1 million preventable fatalities that were reported in 2017 due to exposure to air pollution of which 56% fatalities were due to outdoor PM2.5 and 44% indoor air pollution. 4 Indoor air pollution are pollutants not only generated from indoor sources but are transported indoor through ventilation and openings of the buildings. 5 Outdoor air pollution is the mixture of pollutants emanating from natural and anthropogenic sources such as industrial activities, power generation, domestic heating, cooking, and transportation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies about the influence of climate variables on air pollutants i.e. particulate matter and sulphur dioxide [38][39][40][41][42][43][44][45][46][47]. In another research, a relationship was found between sulphur dioxide and some climate elements [48].…”
Section: Introductionmentioning
confidence: 99%